A novel indicator in evaluating endoscopic orbital decompression for thyroid-associated orbitopathy - Shi, Jieliang; Pan, Zhaoqi; Tu, Yunhai; Liu, Zhirong; Dong, Siyu; Gao, Yuwan; Li, Wentao; Yang, Jian; Wu, Wencan (Frontiers in Endocrinology, 2025)
ObjectiveTo introduce the increase rate of effective orbital volume (IREOV) as a novel indicator for evaluating outcomes of endoscopic orbital decompression in thyroid-associated orbitopathy (TAO).MethodsIn this retrospective study, 69 subjects (124 orbits) underwent either medial wall decompression (MWD) or lateral wall decompression (LWD) combined with fat decompression for TAO. Artificial intelligence was used to segment the orbit and calculate IREOV to compare MWD and LWD effectiveness. The impact of postoperative extraocular muscle expansion on IREOV was also assessed, with patients categorized into muscle hypertrophy and fat hyperplasia groups.ResultsUsing Artificial Intelligence OrbitNet system, the average IREOV was 0.14 ± 0.08. Postoperative IREOV was significantly higher for MWD (0.17 ± 0.07) than for LWD (0.05 ± 0.05) (P<0.001). Medial rectus muscle expansion had the greatest impact on IREOV after MWD, while lateral rectus muscle expansion affected IREOV after LWD. Most importantly, TAO patients with muscle hypertrophy exhibited higher IREOV after MWD compared to those with fat hypertrophy (P<0.001). Proptosis reduction was 3.20 ± 1.37mm for MWD and 3.02 ± 0.68mm for LWD, with no significant difference (P>0.05).ConclusionAccurate IREOV calculation through artificial intelligence is crucial for evaluating the efficacy of orbital decompression surgery. For TAO patients presenting with fat hyperplasia, LWD should be prioritized to minimize the risk of postoperative extraocular muscle expansion. In cases where MWD is performed on fat hyperplasia patients, rigorous postoperative surveillance for extraocular muscle expansion is essential.